Main tendencies in the category of number in Japanese and Swahili - Nailya Gabdelkhamitovna Mingazova, Vitaly Glebovich Subichm,; Ali Al-foadi, Raheem (Opción, 2019)
This article deals with comparing the main tendencies of the number category in two non-related languages: Swahili (Bantu language family) and Japanese via comparative qualitative research methods. As a result, Japanese and Swahili possess similar and different markers of abstraction and unification, retaining some peculiarities of primitive mentality. In conclusion, languages of isolated communities, such as Japanese and Swahili, demonstrate tendencies to unify/abstract certain grammatical categories (such as the number category), however, retain some peculiarities of the primitive mentality and ancient thinking.